Advances in Marine Biology : vol. 18 - Blaxter, J. H. S.; Russell, Frederick S.; Yonge, Maurice (Academic Press [Imprint] San Diego : Elsevier Science & Technology Books, 1980)
Annotation This volume of Advances in Marine Biology contains four eclectic reviews on topics ranging from marine mollusc mucus to deep-sea hydrothermal vent fauna.Advances in Marine Biology contains up-to-date reviews of all areas of marine science, including fisheries science and macro/micro fauna. Each volume contains peer-reviewed papers detailing the ecology of marine regions.
Keywords: Marine biology